PENGARUH PROFITABILITAS, LEVERAGE DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA - Vanessa Chandra; Jhon Raphael Saragih (LPPM STIE Muhammadiah Bandung, 2022)
This study aims to examine the relationship between Profitability, Leverage, and Deferred Tax Expense on Earnings Management in Agricultural Sector Companies listed on the Indonesia Stock Exchange 2016-2021. This research is a quantitative research with research data is secondary data. The population in this study amounted to 31 companies. The sampling method is purposive sampling in order to obtain a total sample of 7 companies. The analysis technique used is statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of this study indicate that partially profitability has no effect and no significant on earnings management, leverage has a significant positive effect on earnings management, and deferred tax expense has a significant negative effect on earnings management. Simultaneously shows that profitability, leverage, and deferred tax expense have a significant effect on earnings management.